Stakeholder Interactions in Plastic Waste Management along The Ciliwung Riverbanks in DKI Jakarta - Ferry Fauzi Fauzi; Widiatmaka; M Ekayani; I Firmansyah; M. R Cordova (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2026)
Plastic waste management represents a sustainable development challenge, particularly in urban riverbank areas such as the Ciliwung River in DKI Jakarta. Plastic waste management along riverbanks involves multiple actors with diverse roles, including government institutions, local communities, community organizations, universities, the private sector, and non-governmental organizations. This study aims to develop an actor-based model of plastic waste management along the Ciliwung riverbanks in DKI Jakarta using the MACTOR method. Actor identification was conducted through a literature review and interviews with key informants. The results indicate that the Balai Besar Wilayah Sungai Ciliwung Cisadane, universities, and the private sector function as dominant actors influencing policy directions in waste management. Local government agencies, technical implementation units, community organizations, and residents serve as key relay actors in policy implementation, while the informal sector represents dependent stakeholders with tangible contributions but limited involvement in decision-making processes. All actors support efforts to reduce the volume of plastic waste along the Ciliwung Riverbanks, accompanied by improvements in river water quality and reductions in public health risks.